Interactions between the trianionic ligand-centred redox-active metalloligand [CrIII(perfluorocatecholato)3]3− and guest metal ions1. Issue 32 (28th August 2015) - Wakizaka, Masanori; Matsumoto, Takeshi; Kobayashi, Atsushi; Kato, Masako; Chang, Ho-Chol
<x xml:space="preserve">Abstract</x> The redox behavior of redox-active metalloligand (RML), [CrIII(F4Cat)3]3− (F4Cat: perfluorocatecholato), responsible for interaction with guest metal ions in solution are systematically demonstrated.